Design and psychometric evaluation of RES-PRIM: a resilience scale for primary education students with and without neurodevelopmental disorders - Flores-Buils, Raquel; Andrés-Roqueta, Clara; Mateu-Pérez, Rosa (Frontiers in Psychiatry, 2025)
BackgroundPromoting resilience is a proven pathway to well-being, participation, and quality of life in childhood; it is particularly critical for learners with neurodevelopmental disorders (NDD), who encounter layered academic and socio-emotional challenges. Yet existing resilience measures rarely target the 6- to 12-year age band and none offer the inclusive, visually supported format required by many neurodivergent pupils.ObjectiveTo design and provide evidence of validity and reliability for RES-PRIM, a child-friendly, picture-augmented scale that captures both individual strengths (e.g., self-esteem, problem-solving) and contextual supports (e.g., family, peer, and teacher backing) in children with and without NDD.MethodAfter an evidence-guided item-generation process rooted in universal-design principles, RES-PRIM was administered to 529 Spanish primary-school students (465 typically developing, 64 with NDD). Confirmatory factor analysis (CFA) was conducted to provide evidence of validity regarding internal structure, and reliability was examined for the overall scale and each factor using Cronbach’s alpha and McDonald’s omega. In addition, external measures of emotional regulation and academic stress were applied to analyze evidence of relations to external variables.ResultsCFA supported a nine–first-order/two–second-order structure with excellent fit (χ²/df = 1.61, RMSEA= .038, SRMR= .045, CFI= .934, TLI= .922). Reliability was satisfactory for the total scale and all dimensions, with Cronbach’s alpha ranging from.70 to.87 and McDonald’s omega from.72 to.88. Evidence of relations to external variables emerged through the expected associations: higher resilience correlated with better emotion regulation and lower academic stress.ConclusionsRES-PRIM provides researchers and practitioners with a robust, inclusive assessment tool that can (a) identify resilience profiles in diverse classrooms, and (b) guide evidence-based, multi-tiered interventions aimed at enhancing children’s quality of life and full participation.